2012
DOI: 10.1111/j.1365-2923.2011.04195.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating cognitive ability, knowledge tests and situational judgement tests for postgraduate selection

Abstract: OBJECTIVES This study aimed to evaluate the validity and utility of and candidate reactions towards cognitive ability tests, and current selection methods, including a clinical problemsolving test (CPST) and a situational judgement test (SJT), for postgraduate selection.METHODS This was an exploratory, longitudinal study to evaluate the validities of two cognitive ability tests (measuring general intelligence) compared with current selection tests, including a CPST and an SJT, in predicting performance at a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 29 publications
2
79
0
1
Order By: Relevance
“…Although this seems a conceptual gap to us, there is some evidence that SJTs predict performance in one medical training context, that of UK general practice training (Lievens and Patterson 2011) (and the wider literature also suggests that the way an individual responds to an SJT question does predict actual behaviour and performance once in a role (e.g., McDaniel et al 2001)). Validity studies have also shown that SJTs add incremental validity when used in combination with other predictors of job performance such as structured interviews, tests of IQ and personality questionnaires (O'Connell et al 2007;McDaniel et al 2007;Koczwara et al 2012). While the focus of this paper is not to analyse the conceptual and theoretical frameworks of personality tools, it is essential that these are critically examined in order to develop, evaluate and compare medical selection tools and how these are used in admissions/selection processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this seems a conceptual gap to us, there is some evidence that SJTs predict performance in one medical training context, that of UK general practice training (Lievens and Patterson 2011) (and the wider literature also suggests that the way an individual responds to an SJT question does predict actual behaviour and performance once in a role (e.g., McDaniel et al 2001)). Validity studies have also shown that SJTs add incremental validity when used in combination with other predictors of job performance such as structured interviews, tests of IQ and personality questionnaires (O'Connell et al 2007;McDaniel et al 2007;Koczwara et al 2012). While the focus of this paper is not to analyse the conceptual and theoretical frameworks of personality tools, it is essential that these are critically examined in order to develop, evaluate and compare medical selection tools and how these are used in admissions/selection processes.…”
Section: Discussionmentioning
confidence: 99%
“…These can be grouped into ''paper and pencil'' assessments of personality traits (e.g., Adams et al 2012Adams et al , 2015Bore et al 2005a, b;Dowell et al 2011;Fukui et al 2014;James et al 2013;Lumsden et al 2005;Manuel et al 2005;Nedjat et al 2013), structured multiple interview approaches (Dore et al 2010;Eva et al, 2004aEva et al, , b, 2009Hofmeister et al 2008Hofmeister et al , 2009O'Brien et al 2011;Reiter et al 2007;Roberts et al 2008;Rosenfeld et al 2008), selection centres (Gafni et al 2012;ten Cate and Smal 2002;Ziv et al 2008;Gale et al 2010;Randall et al 2006a, b) and-the ''new kid on the block''-situational judgement tests (Christian et al 2010;Koczwara et al 2012;Lievens 2013;Lievens et al 2008;Patterson et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the use of SJTs for selection into medical school have shown that these beneficial characteristics of SJTs also apply in a medical school context (Koczwara et al 2012;Lievens 2013;Lievens et al 2005;Lievens and Sackett 2012;Patterson et al 2009Patterson et al , 2011Patterson et al , 2015.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…While the dominant traits of intelligent females are innovation and responsibility, the dominant traits of males are risk taking and innovation. Such results may help in selecting the right candidates as many studies indicated that the most predictive variables of future performance of recent college graduates are personality and mental ability (Koczwara, 2012;Sjoberg et al, 2012;Marcus et al, 2009;Cook, 2009;Schmidt, Shaffer, & OH, 2008;Rode et al, 2008;Schmidt & Hunter, 2004;Gottfredson, 1997).…”
Section: Discussionmentioning
confidence: 99%